Preparation method of SiO2-based double-covalent network super-hydrophobic composite coating
Through the SiO2-based bicovalent network superhydrophobic composite coating preparation method, the challenges of superhydrophobic surface in mechanical stability and large-scale preparation are solved, and the excellent superhydrophobicity, mechanical stability and various stability characteristics of the coating are achieved.
Patent Information
- Application Number
- CN202510057551.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-14
AI Technical Summary
The existing superhydrophobic surfaces have great challenges in mechanical stability and large-scale preparation, and it is difficult to take into account both superhydrophobic properties and mechanical durability.
SiO2-based bicovalent network superhydrophobic composite coating preparation method is used to synthesize silica nanoparticles through tetraethoxysilane, surface modification is used using perfluorooctyl triethoxysilane, and silane coupling agent and aluminum nitrate nohydrate are introduced to form a covalent network. Finally, epoxy resin is used as the bonding layer to improve adhesion.
The prepared coating has excellent superhydrophobicity, mechanical stability, chemical stability and thermal stability, and is able to wear continuously under high pressure and maintain superhydrophobicity in acidic or alkaline solutions and at high temperatures.
Smart Images

Figure CN119799044A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of super-hydrophobic composite coatings, and in particular to a method for preparing a SiO2-based double covalent network super-hydrophobic composite coating. Background Art
[0002] Since the late 1990s, inspired by natural organisms such as lotus leaves and insect wings, superhydrophobic surfaces have attracted widespread attention due to their self-cleaning, corrosion resistance, oil-water separation, anti-icing, anti-fogging, drag reduction, directional liquid transport, photocatalysis and enhanced buoyancy, and have shown great application potential in various fields. Generally, the contact angle (CA) of a water droplet on a superhydrophobic surface is greater than 150° and the rolling angle (RA) is less than 10°, which allows the water droplet to roll freely and maintain a nearly spherical shape. Surface roughness and low surface energy are necessary factors for artificially constructing superhydrophobic surfaces. Appropriate surface roughness is usually achieved by micro / nanostructures, which can support droplets to reach the Cassie-Baxter state; while low surface energy can ensure that the surface has a sufficiently large contact angle to prevent droplets from wetting the micro / nanostructure due to capillary forces. At present, research on the construction of superhydrophobic surfaces has been relatively mature, but there are still great challenges in the stability and large-scale preparation of superhydrophobic surfaces.
[0003] Mechanical stability is the key characteristic that determines whether a super-hydrophobic surface can be applied in practice. Usually, the micro / nano rough structure of a super-hydrophobic surface is very fragile and easily damaged, causing the coating to lose its super-hydrophobic effect and thus lose its functional characteristics. At present, several strategies have been extended to improve the mechanical strength by using adhesives such as epoxy resins, silicone resins and commercial adhesives. Usually, the method to improve the mechanical strength of a super-hydrophobic surface is mostly to apply a layer of adhesive between the micro-nano coating and the substrate. During the curing process of the adhesive, the micro-nano particles will be partially embedded. This method can only ensure the mechanical strength of a small layer of coating particles in contact with the adhesive, and it is still essentially impossible to take into account both mechanical strength and super-hydrophobic properties; another method is to mix some adhesives in the middle of the hydrophobic particles to act as a binder between the super-hydrophobic micro-nano particles, but when using this method, the amount of adhesive should not be too much, otherwise the nanoparticles will be completely wrapped, causing the surface to lose its roughness, and the hydrophobic property will be weakened. Therefore, the super-hydrophobic property is often lost before the mechanical strength is significantly improved, and it is still impossible to achieve a balance between the two.
[0004] Therefore, it is necessary to explore a low-cost, easy-to-promote method for preparing superhydrophobic surfaces that can take into account both superhydrophobic properties and mechanical durability. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a method for preparing a SiO2-based double covalent network super-hydrophobic composite coating.
[0006] The method for preparing a SiO2-based bicovalent network super-hydrophobic composite coating provided by the present invention comprises the following steps:
[0007] S1, using tetraethoxysilane as raw material, through Method, synthesis of silica nanoparticles;
[0008] S2, using perfluorooctyltriethoxysilane as a surface modifier to modify the surface of silica nanoparticles to obtain superhydrophobic silica nanoparticles;
[0009] S3, introducing a silane coupling agent and aluminum nitrate nonahydrate to generate a Si-O-Si covalent network and an Al-O-Al covalent network, respectively;
[0010] S4. Use epoxy resin as a bonding layer to adhere the coating to the substrate to form a composite coating to improve the adhesion of the nano coating.
[0011] The preferred synthesis steps of silica nanoparticles include:
[0012] Add 1 part of tetraethoxysilane to 5 parts of ethanol and mix thoroughly to form component A;
[0013] Add 0.36 parts of aqueous ammonia and 0.6 parts of water to another 5 parts of ethanol and mix thoroughly to form component B;
[0014] Under magnetic stirring at 500 rpm, component A was added dropwise to component B to prepare hydrophilic SiO2 nanoparticles.
[0015] Preferably, the surface modification step comprises:
[0016] Add 0.1 parts of perfluorooctyltriethoxysilane, 0.4 parts of vinyltriethoxysilane and aluminum nitrate nonahydrate to the hydrophilic SiO2 sol;
[0017] After ultrasonic treatment at 45 °C for 1 h, an integrated super-hydrophobic coating was obtained.
[0018] Preferably, in step S4, the step of preparing the composite coating comprises:
[0019] The epoxy resin and the curing agent polyamide resin were mixed in a mass ratio of 1:1, dissolved in ethanol and mixed evenly to form a solution with an epoxy resin concentration of 0.1 g / mL;
[0020] The mixed solution was sprayed on the pretreated substrate at a spraying distance of 20 cm;
[0021] Use a spray gun to spray the prepared super hydrophobic coating on the epoxy resin coating that has been initially cured for 3 hours at room temperature, and the spraying distance is also 20 cm;
[0022] The sprayed sample was placed in an oven at 150 °C for 10 h to completely evaporate the solvent ethanol and solidify it to obtain a super hydrophobic surface of the double covalent network, which was labeled as F-SiO 2 / VTES / AlO x / EP coating.
[0023] Preferably, the substrate is a glass slide, and may also be a silicon wafer, a 1060 pure aluminum sheet, a 6061 aluminum alloy sheet, a copper sheet and a ceramic sheet. The metal substrate is polished in the direction of the surface texture with 600 mesh and 2000 mesh SiC sandpaper in sequence, and then ultrasonically cleaned with ethanol and dried in an oven at 60°C; the non-metallic substrate only needs to be cleaned in the same way.
[0024] Compared with the related art, the method for preparing the SiO2-based double covalent network super-hydrophobic composite coating provided by the present invention has the following beneficial effects:
[0025] The prepared coating has excellent superhydrophobicity, with a contact angle greater than 162° and a sliding angle of about 6°;
[0026] The coating exhibits good mechanical stability and can sustain wear for more than 5600 cm at a pressure of 541 Pa;
[0027] The coating has excellent chemical stability and can remain superhydrophobic after being immersed in acidic or alkaline solutions for several hours;
[0028] The coating has good thermal stability and can maintain superhydrophobicity at temperatures up to 300°C;
[0029] The preparation method of the coating is simple and suitable for large-scale industrial manufacturing. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 are the structural formulas of (a) TEOS, (b) POTS, and (c) VTES in the present invention;
[0031] Figure 2 Schematic diagram of contact angle and sliding angle of different coatings: (a) F-SiO2 (RA = 5.05°); (b) F-SiO2 / VTES (RA = 4.80°); (c) F-SiO2 / VTES / AlO x (RA=2.94°); (d) F-SiO2 / VTES / AlO x / EP(RA=6.62°);(e)SiO2;(f)bare glass;
[0032] Figure 3SEM images of different surfaces: (a) SiO2 coating; (b) F-SiO2 coating; (c) F-SiO2 / VTES coating; (d) F-SiO2 / VTES / AlO x Coating; (e) F-SiO2 / VTES / AlO x / EP coating;
[0033] Figure 4 EDS test results and element mass and atomic number ratios (embedded table): (a) SiO2 coating; (b) F-SiO2 coating; (c) F-SiO2 / VTES coating; (d) F-SiO2 / VTES / AlO x coating;
[0034] Figure 5 SiO2 nanocomposites, F-SiO2 nanocomposites, F-SiO2 / VTES nanocomposites, F-SiO2 / VTES / AlO x FTIR spectra of nanocomposites;
[0035] Figure 6 The following are: (a) experimental diagram of the self-cleaning ability of the composite coating; (b) schematic diagram of the self-cleaning characteristics;
[0036] Figure 7 : (a) Schematic diagram of sandpaper wear test of super-hydrophobic coating; (b) Changes of contact angle and rolling angle of different surfaces with the number of wear cycles;
[0037] Figure 8 The following are: (a) the contact angle of droplets with different pH values on the super-hydrophobic surface; (b) the curves of the contact angle and the rolling angle of the coating changing with the immersion time; (c) the curves of the contact angle and the rolling angle changing with the temperature;
[0038] Fig. 9 : (a) Preparation mechanism of SiO2 super-hydrophobic composite coating; (b) Schematic diagram of self-similar characteristics of failure;
[0039] Fig.10 : Photos of water droplets (5.0 μL) on different substrates; the value below each photo is the corresponding contact angle;
[0040] Fig.11 Schematic diagram of the preparation process of a SiO2-based double covalent network super-hydrophobic composite coating provided by the present invention: (a) SiO2 nanoparticles; (b) nanoparticle surface modification and covalent coupling; (c) F-SiO2 / VTES / AlO x / EP composite coating. DETAILED DESCRIPTION
[0041] The present invention will be further described below in conjunction with the accompanying drawings and implementation modes.
[0042] In this paper, a two-step spraying method is proposed to prepare a superhydrophobic surface with self-similar structure and high wear resistance. Fig.11 As shown, the present invention proposes a method for preparing a SiO2-based double covalent network super-hydrophobic composite coating, using tetraethoxysilane as a raw material, firstly by Methods Silica nanoparticles were prepared, and superhydrophobic silica nanoparticles were obtained by using perfluorooctyltriethoxysilane (POTS) as a surface modifier. Vinyltriethoxysilane (VTES) and aluminum nitrate nonahydrate (Al(NO3)3·9H2O) were introduced to generate silicon-oxygen and aluminum-oxygen covalent networks, respectively. At the same time, low-cost epoxy resin was used as an adhesive layer between the nanoparticles and the substrate to improve the adhesion of the nanocoating.
[0043] The results show that the composite coating has good super-hydrophobicity, has the characteristics of high contact angle and low rolling, and has good mechanical stability. At the same time, the coating exhibits excellent chemical stability and thermal stability, as well as effective self-cleaning properties. In addition, the sol-gel method is used to deposit micro / nanoparticles onto the substrate surface by spraying. This method is more flexible in the choice of materials, has fewer restrictions on the substrate, and is low in cost, making it suitable for large-scale industrial manufacturing. The present invention not only provides a strong and wear-resistant super-hydrophobic surface material, but also provides a simple manufacturing strategy for future industrial applications.
[0044] Next, the preparation method of the SiO2-based double covalent network super-hydrophobic composite coating proposed in the present invention will be described in detail through the following experimental method.
[0045] 1. Experiment
[0046] 2.1. Materials
[0047] The reagents required for the experiment are shown in the following table:
[0048] Table 1 Summary of chemicals used in the experiment
[0049]
[0050]
[0051] Glass slides (76.2 mm × 25.4 mm × 1 mm) were used as the main substrate for subsequent experiments. Silicon wafers, 1060 pure aluminum sheets, 6061 aluminum alloy sheets, copper sheets, and ceramic sheets were also used, all with a size of 20 mm × 20 mm (≈1 mm thickness). All metal substrates were polished in the direction of the surface texture with 600-mesh and 2000-mesh SiC sandpapers, then ultrasonically cleaned with ethanol and dried in an oven at 60°C. Non-metallic substrates only need to be cleaned in the same way.
[0052] 1.2 Preparation of SiO2-based super-hydrophobic composite coating
[0053] First, 1 mL of TEOS was added to 5 mL of EtOH to form component A, and 0.36 mL of ammonia and 0.6 mL of water were added to another 5 mL of EtOH to form component B. After each component was fully mixed, component A was added dropwise to component B under magnetic stirring at 500 rpm. After preparing SiO2 nanoparticles, 0.1 mL of POTS, 0.4 mL of VTES and 0.0425 g of Al(NO3)3·9H2O were added to the hydrophilic SiO2 sol, and ultrasonic treatment was performed at 45°C for 1 h to obtain an integrated superhydrophobic coating.
[0054] Then, the epoxy resin and the curing agent polyamide resin are mixed in a mass ratio of 1: 1, dissolved in ethanol, and mixed evenly to form a solution with an epoxy resin concentration of 0.1g / mL, which is then sprayed on the pretreated substrate at a spraying distance of 20cm. After initial solidification for 3 hours at room temperature, the prepared super-hydrophobic sol is sprayed on the epoxy resin coating using a spray gun, and the spraying distance is also 20cm. After spraying, the prepared sample is placed in a 150°C oven overnight to completely evaporate the solvent ethanol, and to solidify the epoxy resin and aluminum nitrate, and finally a super-hydrophobic surface of a double covalent network is obtained, labeled as F-SiO2 / VTES / AlO x / EP coating.
[0055] In order to analyze the specific effects of several different additives, we also prepared F-SiO2 coating, F-SiO2 / VTES coating, F-SiO2 / VTES / AlO x The coatings are compared. The F-SiO2 coating is formed by spraying the hydrophobic SiO2 sol that has only been fluorinated, and the F-SiO2 / VTES coating is formed by spraying the hydrophilic SiO2 sol after adding POTS and VTES. Both require ultrasonic treatment at 45°C for 1 hour after adding additives. No curing is required after spraying, and drying at 60°C for 1 hour is sufficient. F-SiO2 / VTES / AlO x The coating preparation process is the same as F-SiO2 / VTES / AlO x / EP coating, the only difference is that no epoxy resin is used as adhesive.
[0056] 1.3 Characterization and Testing
[0057] 1.3.1 Surface characterization methods
[0058] Wettability analysis method:
[0059] The contact angle and rolling angle of the prepared surface were measured using an optical tensiometer (old version OneAttension Theta) produced by Biolin Technology Co., Ltd. of Sweden to characterize the wettability of the coating. A 5 μL drop of deionized water was used for the contact angle measurement, and a 10 μL drop of deionized water was used for the rolling angle measurement.
[0060] Surface morphology analysis method:
[0061] The surface morphology of the prepared coating was observed using a field emission scanning electron microscope (FESEM or SEM) (model JSM-7500) provided by Japan Jieoulu (Beijing) Science and Trade Co., Ltd. The acceleration voltage was 0.1-30 kV and the magnification was 25-1,000,000. Before the test, gold spraying was first performed to improve the conductivity of the sample surface.
[0062] Elemental composition analysis method:
[0063] The energy-dispersive spectroscopy (EDS) probe of the field emission scanning electron microscope was used to analyze the elemental composition of the prepared samples by line scanning.
[0064] Chemical bond composition analysis method:
[0065] The chemical group type of the super-hydrophobic coating was tested using a Fourier transform infrared spectrometer (Attenuated Total Reflectance-Fourier Transform Infrared Spectroscopy, ATR-FTIR or FTIR) (model Nicolet 6700) provided by Thermo Fisher Scientific, USA, to verify the results of surface modification and the generation of covalent networks. The test spectrum range is 400-4000cm -1 , spectral resolution better than 0.09cm -1 , scanning speed is not less than 65 sheets / second (16cm -1 ).
[0066] 1.3.2 Performance Testing Method
[0067] Self-cleaning performance test method:
[0068] The self-cleaning performance was tested using dust. First, we sprinkled dust powder on the prepared superhydrophobic surface, and then during the self-cleaning process, deionized water was continuously dripped on the contaminated surface to observe the surface cleaning condition. Similar tests were performed on the above four coatings and bare glass slides for comparison.
[0069] Mechanical stability test method:
[0070] The mechanical stability of the samples with different coatings was verified by sandpaper wear test. The side of the sample coated with superhydrophobic coating faced down and was in direct contact with 2000 mesh SiC sandpaper. A 100g weight was placed on the back of the sample to provide a pressure of 541Pa. The sample was then dragged along a straight line for 10cm and then moved in the opposite direction for 10cm along the same route on the sandpaper. This process was considered a wear cycle. The contact angle and rolling angle of the coating were measured and recorded at regular intervals. Mechanical stability can be evaluated by the wear distance, which refers to the maximum friction distance that the coating can withstand without losing its superhydrophobicity. At the same time, the SEM images of the coating after wear were observed to compare the changes in the surface morphology of the coating.
[0071] Chemical stability test method:
[0072] In order to verify the chemical stability of the coating, this paper measured the contact angle and rolling angle of deionized water droplets with different pH values ranging from 1 to 13 on the surface of the prepared superhydrophobic coating, and used HCl and NaOH to prepare aqueous solutions with different pH values. In addition, the prepared coating samples were immersed in acid and alkali solutions with different pH values. After a certain time interval, the sample slides were taken out, washed with deionized water, and dried. The contact angle and rolling angle were measured and recorded with deionized water drops to observe the effect on the wettability of the coating after immersion in acid and alkali solutions with different pH values.
[0073] Thermal stability test method:
[0074] In order to verify the thermal stability of the prepared superhydrophobic coatings, the sample sheets of these coatings were placed in a muffle furnace and heated to different temperatures for 1 hour. After each annealing, the contact angle and sliding angle of the coatings were measured and recorded with deionized water.
[0075] 2. Results and Discussion
[0076] 2.1. Wettability analysis
[0077] The contact angle and sliding angle of the prepared coating are as follows Figure 2As shown. First, the contact angles of the bare glass sheet and epoxy resin surface were tested, and the sizes were 28.62° and 71.39° respectively. The water droplets could not roll freely, indicating that both were hydrophilic surfaces (contact angles less than 90°). The contact angle of the SiO2 coating without surface modification was only about 14.65°, close to the range of super-hydrophilicity (contact angle less than 10°). As soon as the water droplets contacted the coating surface, they were quickly absorbed, spread on the coating surface and penetrated all around. This is because the accumulation of SiO2 nanoparticles forms a nano-rough structure, and the surface of the prepared SiO2 nanoparticles has hydrophilic hydroxyl groups. When the water droplets contact the coating surface, they are in a Wenzel wetting state. It is consistent with the Wenzel theory, that is, the roughness makes the hydrophilic surface contact angle smaller.
[0078] A POTS film was deposited on a glass slide by spraying a solution of POTS, water and ethanol mixed and ultrasonically treated for 1 hour. The contact angle was 105.53° and the water droplets were in a hydrophobic state, indicating that POTS has a low surface energy. However, water droplets cannot roll freely on its surface because there is no rough structure on the surface and no air cushion can be formed under the water droplets. The coating sprayed with POTS-modified SiO2 nanoparticles exhibits superhydrophobicity, with a contact angle of 168.32° and a rolling angle of 5.05°. The water droplets appear spherical on the coating surface. This is attributed to the combined effect of the roughness generated by the accumulation of SiO2 nanoparticles and the low surface energy of the POTS conformal thin layer on the surface of the SiO2 particles.
[0079] Adding additives to the coating will not affect its superhydrophobicity, such as F-SiO2 / VTES / AlO x The contact angle of the EP coating remains at around 162.83°, and water droplets can still roll freely on the surface, showing excellent superhydrophobicity. Figure 3 The SEM images show that the air pockets in the nanoscale rough structure are filled with Si-O-Si covalent polymers and AlO x The crystals are partially filled, which reduces the surface roughness and produces excellent superhydrophobicity under the action of the covalent bonds of the nanoparticles. Usually, too high or too low surface roughness will reduce the contact angle.
[0080] Surface morphology and chemical properties
[0081] Surface morphology analysis
[0082] The surface morphology of the prepared coatings was observed using a field emission scanning electron microscope (SEM). Figure 3 As shown. Figure 3a As can be seen, the SiO2 nanoparticles are all spherical and have good monodispersity, which is consistent with previous reports. The accumulation of hydrophobic nanoparticles causes the droplets to form a Cassie-Baxter wetting state on the prepared surface. The average particle size of the particles measured using Nano Measurer software is approximately 400nm.
[0083] By comparison Figure 3 a and Figure 3 The SEM photo of b shows that the simple modification of POTS hardly changes the surface morphology of the nanoparticles. The SiO2 microspheres provide nanoscale surface roughness, allowing the droplets to be supported to form an air cushion, and the POTS modification provides low surface energy. The two work together to form a Cassie-Baxter wetting state on the prepared surface. However, when VTES is added, a Si-O-Si covalent network is formed between the particles, such as Figure 3 As shown in c, SiO2 nanoparticles are wrapped by polysilsesquioxane matrix. When aluminum nitrate is added to form an Al-O-Al covalent network, by comparison Figure 3 c and Figure 3 d It can be seen that some AlO is newly added between particles. x Crystal. By contrast Figure 3 d and Figure 3 It can be found that the use of epoxy resin hardly changes the surface morphology of the coating, except that the SiO2 nanoparticles are partially embedded in the epoxy resin layer. The SEM test proves the effectiveness of using the composite method to enhance the mechanical stability from the micro-nano structure of the coating, providing theoretical support for the design of micro-nano structure.
[0084] Elemental composition analysis
[0085] In addition to surface morphology and wettability, this paper also used energy dispersive spectroscopy (EDS) to analyze the surface elemental composition and element distribution of a series of POTS-modified coatings. Figure 4 As shown in the figure, SiO2 coating, F-SiO2 coating, F-SiO2 / VTES coating and F-SiO2 / VTES / AlO coating were analyzed by line scanning. x Elemental composition of nanocomposites.
[0086] For the SiO2 nanocoating, the element peaks of Si and O can be observed, and the atomic ratio of Si and O is 25.45:75.45, which is close to the theoretical value of 1:2 for SiO2 nanoparticles. This indicates that TEOS has completed the hydrolysis and condensation reaction, and the reason for the slightly higher content of O element may be that SiO2 nanoparticles contain a certain amount of water. Compared with SiO2, the F-SiO2 nanocoating has two more elements, C and F, and the atomic ratio of C and F is 13.92:20.36, which is very close to the atomic ratio of C and F on the POTS molecular branch chain of 8:13, indicating that POTS has been successfully modified on the surface of silica nanoparticles, that is, the fluorocarbon long chain has been successfully grafted on the particle surface, introducing the two elements C and F, reducing the surface energy, and changing the coating from superhydrophilic to superhydrophobic. Compared with the F-SiO2 coating, the F-SiO2 / VTES nanocomposite material does not introduce new elements, and the element peaks of Si, O, C and F can be observed, while the F-SiO2 / VTES / AlO x The element peak of Al can also be observed. This indicates that Al(NO3)3·9H2O is fully decomposed under heating conditions to form AlO x The covalent network improves the mechanical strength of the coating. The chemical reaction equation for the decomposition of Al(NO3)3·9H2O is shown in Equation 1. The lack of N element may be due to its overflow with NO2.
[0087] 4Al(NO3)3·9H2O→2Al2O3+12NO2+3O2+36H2O(1)
[0088] Chemical bond composition analysis
[0089] ATR-FTIR was used to analyze the chemical bond composition of a series of POTS-modified coatings. Figure 5 As shown. 3423cm -1 The absorption peak at 1633cm is formed by the stretching vibration of hydroxyl (-OH). -1 There is a bending vibration absorption peak of HOH at 1100 cm -1 and 456cm -1 The two absorption peaks at 801cm -1 At 957cm -1 The bending vibration absorption peak of Si-OH group is at 1243cm, indicating that there are still some unmodified hydroxyl groups on the surface of the prepared SiO2 nanoparticles. -1 It is the stretching vibration peak of the CF bond, indicating that the fluorocarbon long chain of POTS is successfully grafted onto the surface of SiO2 nanoparticles. -1 and 2958cm-1 The asymmetric and symmetric stretching vibration peaks of the -CH2 group are 1647 cm -1 and 750cm -1 The peaks are the stretching vibration peaks of C=C bond and Si-C bond, which means that VTES is successfully introduced into the system and improves the mechanical strength of the coating. It can be seen that with the addition of different reactants, the corresponding chemical groups are successfully introduced into the coating prepared in this paper, proving that the introduction of these groups can reduce the surface energy of nanoparticles while improving the mechanical strength of the coating. The test results are in line with expectations.
[0090] 2.3. Analysis of self-cleaning performance
[0091] The self-cleaning properties of superhydrophobic surfaces have enormous practical applications, such as reducing the maintenance costs of solar panels, air conditioners, and building facades by addressing particle contamination. Figure 6 As shown, in this experiment, dust was used to contaminate the super-hydrophobic surface.
[0092] Tilt the sample at an angle of 10° and continue to drip deionized water onto the super-hydrophobic surface. Figure 6 As shown in a, it can be seen that the water droplets continuously carry away the dust and powder on the surface while rolling down. The reason why the superhydrophobic surface has self-cleaning properties is similar to the reason why the superhydrophobic wetting state is formed. On the one hand, it is the low surface energy of the superhydrophobic surface, and on the other hand, the air cushion formed by the nano-scale rough structure of the surface makes the dust particles and the superhydrophobic surface have a smaller contact area. The combined effect of the two makes the superhydrophobic surface have very little adhesion to dust particles, which is much smaller than the adhesion of water droplets to dust particles. Therefore, water droplets can carry away dust particles when rolling down. The schematic diagram of the self-cleaning property is shown in Figure 6 As shown in b.
[0093] As a comparison, the same experiment was carried out on a bare glass sheet, but the dust powder was wetted and remained on the glass surface, such as Figure 6 It is worth noting that on the surface of the F-SiO2 coating in the figure, a portion of the super-hydrophobic SiO2 white powder will be carried away when the water droplets roll. This is because the coating does not contain a mechanical strength enhancer and the bonding force between the nanoparticles is low. This also indirectly confirms that when contaminated by hydrophobic particle powder, the coating still has good self-cleaning properties.
[0094] 2.4. Coating stability and durability
[0095] Mechanical stability analysis
[0096] In this paper, the sandpaper grinding method is used to analyze the mechanical stability of the coating. Figure 7As shown in a, the coated side of the sample piece faces downward and is in direct contact with the gauze paper. A 100g weight is placed on the back of the sample piece. The sample piece is pushed back and forth with tweezers. The contact angle and rolling angle of the coating are measured once every certain wear cycle interval. Figure 7 The results of b show that the super-hydrophobic coating modified only with POTS is the most fragile. After 6 wears, the contact angle of the coating drops to below 150 °, and the super-hydrophobic performance is lost. In the experiment, after 6 wears, the water droplets can no longer roll freely on the coating surface. After adding VTES, after about 1000cm of 50 wear cycles, the coating loses super-hydrophobicity, which shows that the mechanical strength of the coating is enhanced. If VTES is added together with aluminum nitrate, the wear distance is increased to about 2000cm, indicating that the mechanical strength of the coating is further enhanced. After using epoxy resin as the bonding layer between the coating and the surface, the contact angle of the coating drops to below 150 ° after 280 wear cycles, and the wear distance that the coating can withstand is about 5600cm, and compared with simple physical deposition, the use of the bonding layer significantly improves the mechanical strength of the coating.
[0097] Chemical stability analysis
[0098] The promotion and application of super-hydrophobic coatings is inseparable from their highly stable chemical properties. This article measures the contact angle of water droplets with different pH values on the surface of the prepared super-hydrophobic coating, as well as the method of immersing in strong acid and strong alkali to measure the acid and alkali corrosion resistance of the prepared coating. Although such extremely harsh conditions are not common in daily life, such means can effectively test the corrosion resistance of the coating.
[0099] First, the contact angles of water droplets with different pH values on the coating were measured, such as Figure 8 As shown in a, acidic and alkaline water droplets dyed in different colors by litmus are spherical. The contact angles of water droplets with different pH values are not much different, only decreasing slightly in the alkaline area, but still exceeding 160°, which shows that the pH value of the droplet has little effect on the wettability of the coating.
[0100] In order to further explore the coating's tolerance to acid and alkaline solutions, this paper also conducted immersion experiments in acid and alkaline solutions. Figure 8 b It can be seen that the acidic solution has an effect on the prepared F-SiO2 / VTES / AlO xThe wettability of the / EP composite coating is not greatly affected. After more than 30 hours of immersion in HCl solutions at pH = 1 and pH = 2, the contact angle of the coating is still more than 150°, and the rolling angle is less than 10°, maintaining super hydrophobic properties. After more than 36 hours of immersion in NaOH solution at pH = 12, the contact angle of the coating is 162.28°, and the rolling angle is 2.13°, maintaining super hydrophobic properties; after immersion in NaOH solution at pH = 13 for 40 minutes, the contact angle drops to 136.02°, losing the super hydrophobic properties. This phenomenon is due to the fact that the coating is prepared based on SiO2 nanoparticles, and SiO2 can react with strong alkaline substances.
[0101] Thermal stability analysis
[0102] In order to verify the thermal stability of the coating, this paper conducted repeated heating and annealing experiments on the coating in a muffle furnace. Figure 8 As can be seen in c, below 300°C, the contact angle and rolling angle of the coating do not change much, indicating that the wettability has hardly changed. However, starting from 300°C, the hydrophobicity of the coating begins to decline, the contact angle decreases significantly, and it cannot roll freely on the coating surface, but it still maintains hydrophobicity. When the temperature reaches 400°C, the coating completely loses its hydrophobicity and spreads directly on the coating surface. The change in wettability at high temperature may be due to the decomposition of organic matter on SiO2 nanoparticles.
[0103] 2.5. Analysis of stability mechanisms
[0104] This paper uses two strategies, self-similar properties and adhesive layer, to solve the mechanical durability problems faced by super-hydrophobic coatings in the past. Fig. 9 As shown. The self-similar properties are achieved in two ways. The first is to use VTES, which cross-links SiO2 nanoparticles to form a three-dimensional covalent network - polysilsesquioxane network after hydrolysis and condensation. A similar method is to directly form nanoparticles cross-linked by Si-O-Si bonds through vapor deposition, but its preparation cost is high and its scalability is poor. Another method is to use aluminum nitrate, which decomposes into Al2O3, i.e. AlO under heating conditions. x The covalent network, in addition to acting as a frame to fix the particles, can also support the coating. Epoxy resin is used as a bonding layer to improve the adhesion between the coating and the substrate. At the same time, epoxy resin, as an elastomer, can also reduce the peak stress generated by sandpaper wear to a certain extent.
[0105] 2.6. Analysis of substrate universality
[0106] In addition to glass slides, this paper also used several other types of solid materials as substrates to verify the scalability of the coating. Fig.10As shown, the same treatment was also performed on the surfaces of aluminum, aluminum alloy, silicon, pure copper, ceramics, etc. The test results show that the prepared coating exhibits good superhydrophobic properties on these types of substrates, with a contact angle of more than 165° and a rolling angle of approximately 2 to 3°.
[0107] 3. Conclusion
[0108] In summary, we have successfully developed a fluorinated silica-based bicovalent network superhydrophobic composite coating with excellent mechanical, chemical, and thermal stability. The silica nanoparticles were prepared by the method and modified with POTS, VTES and aluminum nitrate to prepare super hydrophobic coatings. By spraying on the substrate treated with epoxy resin, a super hydrophobic composite coating was constructed with a contact angle of more than 165° and a rolling angle of about 2 to 3°, which has excellent super hydrophobicity. Epoxy resin is used as the bonding layer under the composite coating, VTES and aluminum nitrate form Si-O-Si and AlO respectively. x The network together ensures the mechanical and chemical stability of the coating, allowing it to withstand continuous wear for more than 5600cm under a pressure of 541Pa on 2000-grit sandpaper and remain superhydrophobic after being immersed in acidic or alkaline solutions for dozens of hours. In addition, self-cleaning, anti-fouling, substrate universality and heat resistance up to 300°C further enhance its practicality. This work not only provides a rugged and wear-resistant superhydrophobic surface material, but also provides a new strategy for the design of superhydrophobic coatings.
[0109] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a SiO2-based double covalent network super-hydrophobic composite coating, characterized in that: The following steps are involved: S1, using tetraethoxysilane as raw material, through Method, synthesis of silica nanoparticles; S2, using perfluorooctyltriethoxysilane as a surface modifier to modify the surface of silica nanoparticles to obtain superhydrophobic silica nanoparticles; S3, introducing a silane coupling agent and aluminum nitrate nonahydrate to generate a Si-O-Si covalent network and an Al-O-Al covalent network, respectively; S4. Use epoxy resin as a bonding layer to adhere the coating to the substrate to form a composite coating.
2. The method for preparing a SiO2-based double covalent network super-hydrophobic composite coating according to claim 1, characterized in that: The synthesis steps of the silicon dioxide nanoparticles include: Add 1 part of tetraethoxysilane to 5 parts of ethanol and mix thoroughly to form component A; Add 0.36 parts of aqueous ammonia and 0.6 parts of water to another 5 parts of ethanol and mix thoroughly to form component B; Under magnetic stirring at 500 rpm, component A was added dropwise to component B to prepare hydrophilic SiO2 nanoparticles.
3. The method for preparing a SiO2-based double covalent network super-hydrophobic composite coating according to claim 1, characterized in that: The surface modification step comprises: Add 0.1 parts of perfluorooctyltriethoxysilane, 0.4 parts of vinyltriethoxysilane and aluminum nitrate nonahydrate to the hydrophilic SiO2 sol; After ultrasonic treatment at 45 °C for 1 h, an integrated super-hydrophobic coating was obtained.
4. The method for preparing a SiO2-based double covalent network super-hydrophobic composite coating according to claim 1, characterized in that: In step S4, the steps of preparing the composite coating include: The epoxy resin and the curing agent polyamide resin were mixed in a mass ratio of 1:1, dissolved in ethanol and mixed evenly to form a solution with an epoxy resin concentration of 0.1 g / mL; spraying the mixed solution on the pretreated substrate; Use a spray gun to spray the prepared super hydrophobic coating onto the epoxy resin coating after initial curing at room temperature; The sprayed sample was placed in an oven at 150 °C for 10 h to completely evaporate the solvent ethanol and solidify it to obtain a super hydrophobic surface of the double covalent network, which was labeled as F-SiO2 / VTES / AlO x / EP coating.
5. The method for preparing a SiO2-based double covalent network super-hydrophobic composite coating according to claim 1, characterized in that: The substrate is a glass slide, and can also be a silicon wafer, a 1060 pure aluminum sheet, a 6061 aluminum alloy sheet, a copper sheet and a ceramic sheet. The metal substrate is polished along the surface texture direction with 600 mesh and 2000 mesh SiC sandpaper in turn, and then ultrasonically cleaned with ethanol and dried in an oven at 60°C; the non-metallic substrate only needs to be cleaned in the same way.
Citation Information
Patent Citations
Corrosion-resistant super-hydrophobic layered double hydroxide coating for aluminum alloy surface and preparation method and application thereof
CN113318946A
Super-hydrophobic epoxy anticorrosive coating and preparation method thereof
CN115403991A
Epoxy resin-based super-hydrophobic nano composite coating and preparation method thereof
CN118027782A
Preparation method of nano silicon dioxide / fluorocarbon resin durable super-hydrophobic composite coating and application of nano silicon dioxide / fluorocarbon resin durable super-hydrophobic composite coating on wind turbine blade
CN119119812A
Superhydrophobic silicon-aluminum-zirconium composite material and preparation method thereof
WO2018133260A1